Pengaruh Social Media Marketing dan E-Wom Terhadap Keputusan Pembelian pada Dikichi di Kota Malang - Miko Adetiya Saputra; Arni Utamaningsih (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to examine and analyze the influence of Social Media Marketing and E-WOM on Purchase Decisions at Dikichi in Malang City, both partially and simultaneously. The background of this research was driven by the increasingly competitive fast food culinary industry in Malang City, where Dikichi, as a new brand, needed to leverage digital marketing strategies through social media and electronic word-of-mouth communication to encourage consumer purchase decisions.This research employed a quantitative approach using a survey method involving 100 respondents who are Instagram users, followers of Dikichi's official account, and Dikichi consumers in Malang City. The data analysis technique used was multiple linear regression analysis, processed with statistical software. The results showed that the Social Media Marketing variable (X1) and E-WOM variable (X2), both partially and simultaneously, have a positive and significant effect on Purchase Decisions at Dikichi ini Malang City. These findings indicate that the more optimal Dikichi Marketing activities on social media are, and the more positive opinions and reviews shared among consumers electronically, the greater consimers tendency to make a purchase. The implication of these findings it that Dikichi needs to continue strengthening the quality of its content and interaction on social media, as well as encouraging concumers to actively share positive reviews and recommendations, as an effort to sustain and enhance consumer purchase decision amid the intense competition in Malang City fast food culinary industry..